6 - Compassionate Imagination and Respect for Student Diversity1 in Effective Doctoral Supervision in African Universities - Najjuma, Saidah Mbooge (Journal of Higher Education in Africa, 2022)
Achieving the purpose of the doctoral journey through productive interaction requires that the student and supervisor engage with each other’s intellectual views, which means addressing any challenges posed by the student’s diversity. According to Vilakazi (2016), supervisors embrace democratic justice in contributing to society by supervising students, using their expertise to take care of students’ rights, enabling deliberative engagement and exposing them to critical learning. This is done through the interaction of voices, cultures, values and perspectives, amidst differences. Yet, engaging with diversity can bring about uncertainty, anxiety and other discomfort (Nieminin and Valcke 2018), which, if not handled well can be detrimental to a student’s progress. Identifying, accepting and understanding differences and similarities that exist between individual students and supervisors, to fully utilise their talents and abilities during the supervisory relationship, is an important contribution to knowledge creation. This article explores the notion of compassionate imagination2 as a cata yst to realising respect for student diversity in effective doctoral supervision.